OPTICAL, UV AND X-RAY OBSERVATIONS OF THE SYMBIOTIC STAR AG DRACONIS DURING QUIESCENCE AND THE 1994/1995 OUTBURST - Greiner, J.; Bickert, K.; Luthardt, R.; Viotti, R.; Altamore, A.; Gonzales-Riestra, R.; Stencel, R. E. (Одеські астрономічні публікації, 2017)
Optical, UV and X-ray observations of the well known symbiotic star AG Draconis during quiescence and the active phase 1994/1995 are presented. The intensity in the UV region is well correlated with the optical activity. The observed X / ray flux dropped down by a factor of about 100 during the outburst maximum.